(untitled) (Indian Journal of Nematology, 2024)
To develop an effective Integrated Disease Management (IDM) strategy against root disease complex involving rootknot nematode and fungi in Mulberry, a field experiment was conducted in sick soil in RBD with 7 treatments using Furadan (carbofuran 3G), Bioconsortium seperately and in combination. Results revealed that the maximum improvement in plant growth and reduction in nematode-fungal infections parameters was observed in T-6 [Furadan + Bio-consortium + niger oil cake) followed by T-4 (Bio-consortium + niger oil cake] without any significant difference between them, which improved the plant growth parameters ranging from 77.7-87.7 % and 93.8 % plant survival over the control. Nematode-fungal infection parameters were reduced to an extent of 88.0-93.0 %, by keeping the population of nematode and pathogenic fungi extremely below the economic threshold levels (ETL) in the soil. The rest of the treatments were not found significantly superior over T-6 and T-4 and were unable to improve the plant growth parameters or reduce disease severity as desired. Hence, T-4 was found an eco-friendly IDM strategy for management of root disease complex in mulberry besides preventing leaf yield loss.